On Paraguayan Thrichomys (Hystricognathi: Echimyidae): the distinctiveness of Thrichomys fosteri Thomas, 1903 - Dâ€™Elía, Guillermo; Myers, Philip (THERYA, 2014)
Introduction: Thrichomys is a genus of cursorial rodents of the family Echimyidae that is distributed across open tropical ecoregions in central and eastern South America. The understanding of species boundaries within the genus has changed dramatically during the last decade with the widespread usage of chromosomal and molecular data, resulting in an unstable taxonomy. One of the issues recently raised, on the basis of a study of specimens from south central Brazil (Mato Grosso do Sul State), is the distinctiveness at the species level of T. fosteri (with type locality in Paraguay), usually considered a synonym of T. pachyurus. Here we provide the first morphologic, karyotypic and molecular data for a series of Paraguayan specimens of Thrichomys aimed to resolve this taxonomic conundrum. Methodology: Thirty one specimens collected at five Paraguayan localities were morphologically assessed. Descriptive statistics for 20 cranial measurements were calculated for a subset of specimens considered juveniles and for a subset of specimens considered to be adults. Seven specimens of Thrichomys from three Paraguayan localities were karyotyped using standard chromosome techniques. The genetic (p-distance) and phylogenetic (Bayesian inference) analyses were based on the first 801 base pairs of the cytochrome b gene of 15 Paraguayan specimens collected at one locality and 71 Brazilian specimens of Thrichomys that belong to about eight forms of species level. Results: Paraguayan specimens examined closely match Thomas’s (1903) description of Thrichomys fosteri in size and qualitative characters. All specimens have 2n = 34, FN = 64. The Paraguayan sample used for the genetic analysis shows no variation. Observed genetic variation between the Paraguayan haplotype and haplotypes from other populations ranges from 0.5 % to 8.5 %. The phylogenetic analysis show that Paraguayan haplotype falls within the clade (PP = 1) formed by haplotypes of specimens from Mato Grosso do Sul, Brazil and referred by Nascimento et al. (2013) to Thrichomys fosteri. Discussion and conclusions: Our data indicate that in fact Paraguayan populations of Thrichomys belong, together with those of the neighbouring Brazilian state of Mato Grosso do Sul, to a distinct species of Thrichomys to which the name T. fosteri applies. We expect that these data will contribute to a much needed comprehensive revision of the genus. Key words: Eumysopinae, Hystricognathi, Octodontoidea, Paraguay, taxonomy